Comparative efficacy and tolerability of amphotericin B lipid complex and liposomal amphotericin B in the treatment of invasive fungal infections in patients with hematological malignancies: literature review - N. V. Dmitrieva; I. N. Petukhova (Онкогематология)
An overview of the literature data concerning the comparison of toxicity, efficacy and cost of amphotericin B lipid complex and liposomal amphotericin B, as well as their comparison with amphotericin B deoxycholate are provided.